STRATEGI GURU DALAM MENUMBUHKAN KREATIVITAS PESERTA DIDIK PADA PEMBELAJARAN JARAK JAUH DI SD N KALIKUTUK SENTOLO - Kurnia, Afrisnaini Hanna; Putra, Lovandri Dwanda (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
Elementary school students should have developed their creativity through varied learning strategies. Creativity can familiarize students to come up with new ideas, innovate and can produce unique solutions to various problems. The purpose of this study is to describe the teacher’s strategy and find out the supporting and inhibiting factors in fostering creativity in distance learning at SD N Kalikutuk Sentolo. This research is a qualitative research with a case study approach. Data collection techniques using interviews, observations, documentation reviews and questionnaires are then analyses through the data reduction stage, data presentation and conclusion drawing. The subjects of the study were teacher and 5 students of class 4A. test the validity of the data using source triangulation and techniques. The results showed that 1) Teacher strategies in general in fostering creativity, namely through organizing strategies, learning delivery strategies and learning management strategies. 2) Teacher strategies in fostering creativity include give training students to have great curiosity, rich in initiative, interested in creative activities, rich in imagination and confident and independent. 3) Supporting factors in fostering creativity are the most influential, namely environmental factor, personality factor, interest and motivation factor as well as assessment factor, other supporting factors for the existence of sufficient devices during the distance learning process, cooperation between teacher and parents. 4) The inhibiting factor is the erratic network during distance learning. Keywords: Teacher Strategy; Creativity; Distance Learning; Elementary School